Aktivitas Tabir Surya Secara In-Vitro Ekstrak dan Fraksi Daun Kedondong (Spondias dulcis Sol. Ex G.Forst) - Rudiyansyah; Fathurrahman, Rizal; Sayekti, Endah (Jurnal Riset Kimia, 2024)
Excessive sun exposure to the skin can cause redness (erythema) and darkening of the skin (pigmentation). This effect can be prevented by using sunscreen. Kedondong leaves (Spondias dulcis Sol. Ex G. Forst) can act as a natural sunscreen because they contain secondary metabolite compounds with a conjugated double bond structure (chromophore), including phenolic and flavonoid compounds. The presence of conjugated double bonds in phenolic and flavonoid compounds is known to be able to absorb UV radiation thereby reducing its intensity on the skin. This study aims to determine the sunscreen activity of kedondong leaves based on the Sun Protection Factor (SPF), , the percentage of erythema transmission value (%Te), and the percentage of pigmentation transmission value (%Tp) and determine the secondary metabolite groups in kedondong leaf extracts and fractions. The research stages carried out were extraction of kedondong leaves by maceration, dechlorophyllation, followed by fractionation using n-hexane and dichloromethane, to obtain methanol extract, n-hexane fraction, dichloromethane fraction and methanol fraction. Then phytochemical tests were carried out on the extracts and fractions. Phytochemical tests showed that the secondary metabolite compounds in the methanol extract of kedondong leaves were alkaloids, phenolics, steroids and saponins. Furthermore, in the n-hexane fraction are steroids, the dichloromethane fraction is phenolic compounds, and the methanol fraction is alkaloid, phenolic and saponin compounds. Using a UV-Vis spectrophotometer at a wavelength of 200-400 nm, the sunscreen activity test showed that the dichloromethane fraction at a concentration of 120 mg/L was included in the extra protection category with an SPF value of 7,86±0,23; fast tanning with a %Te value of 15,99±0,83 and sunblock with a %Tp value of 32,72±1,09.